Positive electrode active material for lithium-ion rechargeable batteries

By mixing the first and second single crystal lithium transition metal oxide powders in a specific particle size range and proportion, the compression density of the formed positive electrode active material in the positive electrode of the battery is significantly improved, and the problem of low fill density of the existing materials is solved.

JP7665749B2Active Publication Date: 2025-04-21UMICORE(BE)
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2023532403
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-11-27
Filing Date
2021-11-26
Publication Date
2025-04-21
Estimated Expiration
2041-11-26

AI Technical Summary

Technical Problem

The existing single-crystal Li-Ni-Mn-Co or Li-Ni-Co-Al oxide positive electrode active materials have low filling density in the positive electrode of the battery, resulting in a large volume and cannot meet the high density requirements.

Method used

A mixture consisting of the first and second single crystal lithium transition metal oxide powders is used as the positive electrode active material, wherein the median particle size of the first single crystal lithium transition metal oxide powder is between 3 microns and 15 microns, the median particle size of the second single crystal lithium transition metal oxide powder is between 0.5 microns and 3 microns, and the weight fraction of the second powder is between 5% and 40%.

Benefits of technology

Through this mixture, higher compression density is achieved, the problem of low fill density of existing materials in the positive electrode of the battery is solved, and the overall density of the battery is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007665749000002
    Figure 0007665749000002
  • Figure 0007665749000003
    Figure 0007665749000003
  • Figure 0007665749000004
    Figure 0007665749000004
Patent Text Reader

Abstract

The present invention provides a positive electrode active material for a lithium ion rechargeable battery, the positive electrode active material having (i) a median diameter D50 determined by laser particle size distribution analysis. A (ii) a first lithium transition metal oxide having single-crystal particles with a median diameter D50 determined by laser particle size distribution analysis; B a second lithium transition metal oxide containing single-crystal particles having a particle size of 0.5 μm to 3 μm, wherein the weight fraction φ of the second lithium transition metal oxide relative to the total weight of the positive electrode active material is B is 5% by weight to 40% by weight.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a positive electrode active material powder for lithium ion rechargeable batteries.

[0002] In particular, the present invention relates to such cathode materials which are Li-Ni-Mn-Co oxides or Li-Ni-Co-Al oxides and which are formed primarily or entirely from single crystal particles.

[0003] Such monocrystalline positive electrode active material powders are already known, for example from WO 2019 / 185349 A1, a method for preparing a monocrystalline positive electrode active material powder. In its ideal form, the powder consists of dense "monolithic" particles, each particle being a single crystal rather than a secondary particle. Such monocrystalline particles have a higher mechanical strength and thus a better cycling stability in the battery.

[0004] However, due to the presence of a relatively large amount of void space between the particles, the packing density of such active cathode materials in a battery cathode is relatively low, and therefore the volume occupied by such cathodes is relatively large.

[0005] It is an object of the present invention to provide a cathode active material which has the advantage of having a higher density after compaction, and therefore a higher density in a battery electrode, than known single crystal Li-Ni-Mn-Co or Li-Ni-Co-Al oxides. Summary of the Invention

[0006] The object is to provide an active cathode material for a lithium-ion rechargeable battery, the active cathode material comprising Li, a metal M', and oxygen, the metal M' comprising Ni, Co, either Mn or Al, and optionally one or more elements selected from B, Ba, Sr, Mg, Nb, Ti, W, F, and Zr, the active cathode material being a mixture of lithium transition metal oxide powders, the mixture comprises a first lithium transition metal oxide powder and a second lithium transition metal oxide powder, both of which are single crystal powders; The first lithium transition metal oxide powder has a first weight fraction φ of the positive electrode active material. A The first median diameter D50 of 3 μm to 15 μm is determined by laser diffraction particle size distribution analysis. A having The second lithium transition metal oxide powder has a second weight fraction φ of the positive electrode active material. B The second median diameter D50 of 0.5 μm to 3 μm is determined by laser diffraction particle size distribution analysis. B having The second weight fraction φ B This is achieved by providing a positive electrode active material in which the content of the metal oxide is 5% by weight to 40% by weight.

[0007] It is observed that higher packed densities are achieved using the active cathode material according to the present invention, as illustrated by the examples and supported by the results shown in Table 1. EX (Example) 1.4 teaches an active cathode material comprising a first lithium transition metal oxide and a second transition metal oxide, the first single crystal lithium transition metal oxide having a higher median diameter than the second single crystal lithium transition metal oxide.

[0008] For further guidance, figures are included to better understand the teachings of the present invention, which are intended to aid in the explanation of the invention and are not intended to limit the invention of this disclosure. [Brief description of the drawings]

[0009] [Figure 1] 1 shows a scanning electron microscope (SEM) image of a positive electrode active material powder of EX1.4 including a first single crystal lithium transition metal oxide and a second single crystal lithium transition metal oxide. [Diagram 2] FIG. 1 shows a graphical representation of the pressed density (Y-axis, expressed in g / cm3) of EX1.1-1.5 and CEX (comparative example) 1.5 as a function of the weight fraction φB of the second monocrystalline lithium transition metal oxide relative to the total weight of the positive electrode active material (X-axis, expressed in wt%). [Diagram 3]FIG. 1 shows a graphical representation of the pressed density (Y-axis, expressed in g / cm3) of EX1-4 (φB=25 wt.%) and CEX2 as a function of the ratio (D50A / D50B) of D50A of a first monocrystalline lithium transition metal oxide to D50B of a second monocrystalline lithium transition metal oxide (X-axis). [Figure 4] The particle size distributions of samples EX1.4 and EX3.1 are shown, respectively. [Diagram 5] The particle size distributions of samples EX1.4 and EX3.1 are shown, respectively. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] Unless otherwise defined, all terms used in disclosing the present invention, including technical and scientific terms, have the meanings commonly understood by those skilled in the art to which the present invention belongs. With further guidance, definitions of terms are included to better understand the teachings of the present invention. As used herein, the following terms have the following meanings: As used herein, "about" referring to a measurable value such as a parameter, amount, length of time, and the like, is meant to encompass a variation of no more than ±20%, preferably no more than ±10%, more preferably no more than ±5%, even more preferably no more than ±1%, and even more preferably no more than ±0.1% from the specified value, provided such variations are appropriate for the practice of the disclosed invention, although it is to be understood that the value to which the "about" modifier refers is itself specifically disclosed.

[0011] The recitation of numerical ranges by endpoints includes all numbers and fractions subsumed within that range as well as the recited endpoints. All percentages, unless otherwise defined or a different meaning is apparent to one of ordinary skill in the art from their use and the context in which they are used, are understood to be percent by weight, which is abbreviated as "wt. %, " or percent by volume, which is abbreviated as "vol. %, " unless otherwise defined or a different meaning is apparent to one of ordinary skill in the art from their use and the context in which they are used.

[0012] positive electrode active material In a first aspect, the present invention provides a positive electrode active material for a lithium ion rechargeable battery, comprising: the positive electrode active material includes Li, a metal M', and oxygen, the metal M' includes Ni, Co, either Mn or Al, and optionally one or more elements selected from B, Ba, Sr, Mg, Nb, Ti, W, F, and Zr; The positive electrode active material is a mixture of lithium transition metal oxide powders. the mixture comprises a first lithium transition metal oxide powder and a second lithium transition metal oxide powder, both of which are single crystal powders; The first lithium transition metal oxide powder has a first weight fraction φ of the positive electrode active material. A The first median diameter D50 of 3 μm to 15 μm is determined by laser diffraction particle size distribution analysis. A having The second lithium transition metal oxide powder has a second weight fraction φ of the positive electrode active material. B The second median diameter D50 of 0.5 μm to 3 μm is determined by laser diffraction particle size distribution analysis. B having The second weight fraction φ B is 5% by weight to 40% by weight.

[0013] The concept of single crystal powder is well known in the art of cathode active materials. It relates to powders that have mainly single crystal particles. Such powders are a separate class of powders compared to polycrystalline powders that are made of mostly polycrystalline particles. Those skilled in the art can easily distinguish between such two classes of powders based on microscopic images.

[0014] Single crystal particles are also known in the art as monolithic particles, integral particles or / and monocrystalline particles.

[0015] A technical definition of a single crystal powder is not necessary since such powders can be readily recognized by one skilled in the art using an SEM, however, in the context of the present invention, a single crystal powder may be considered to be defined as a powder in which 80% or more of the particles by number are single crystal particles. This means a powder having a size of at least 45 μm by at least 60 μm (i.e., at least 2700 μm2 ), preferably at least 100 μm×100 μm (i.e., at least 10,000 μm 2 ) can be determined from SEM images with a field of view of 100 nm.

[0016] A single crystal particle is a particle that is an individual crystal or is formed from fewer than five, preferably a maximum of three, primary particles that are themselves individual crystals. This can be seen by observing the grain boundaries with a suitable microscopic technique, such as a scanning electron microscope (SEM).

[0017] In determining whether a particle is a single crystal particle, grains having a maximum linear dimension observed by SEM that is smaller than 20% of the median diameter D50 of the powder as determined by laser diffraction are ignored. This avoids inadvertently considering particles that are essentially single crystal but have some very small other grains, e.g., polycrystalline coatings deposited on them, as not being single crystal particles.

[0018] The inventors have found that a higher pressed density can be achieved with the cathode active material for lithium ion rechargeable batteries of the present invention. This is illustrated by the examples, the results of which are shown in Table 1. In EX1.4, the cathode active material has a median diameter D50 of 8.7 μm. A A first lithium transition metal oxide powder having single crystal particles having a median diameter D50 of 1.1 μm. B and a second lithium transition metal oxide powder comprising single crystal particles having the formula:

[0019] Preferably, the present invention provides a second weight fraction φ B The first weight fraction φ is between 15% and 30% by weight, preferably between 20% and 25% by weight, and more preferably equal to 15, 20, 25, 30% by weight or any value therebetween. A and the second weight fraction φ BThe sum of is at least 95%, preferably at least 99%, and more preferably 100%.

[0020] Preferably, the present invention provides a first median diameter D50 A and the second median diameter D50 B The present invention provides a positive electrode active material according to a first aspect of the present invention, wherein the ratio of R to R is between 4 and 30. Preferably, the ratio is between 5 and 15, and more preferably, the ratio is equal to 5, 7, 9, 11, 13, 15, or any value therebetween.

[0021] In a preferred embodiment, the cathode active material according to the first aspect of the invention has a compressibility of at least 3.25 g / cm, determined after application of a uniaxial pressure of 207 MPa for 30 seconds. 3 Preferably, the positive electrode active material has a compressed density of at least 3.50 g / cm 3 , at least 3.55 g / cm 3 , at least 3.60 g / cm 3 , or even at least 3.65 g / cm 3 , or in particular at least 3.70 g / cm 3 Preferably, the positive electrode active material has a compressed density of at most 3.90 g / cm 3 , up to 3.85g / cm 3 , up to 3.80g / cm 3 , up to 3.75g / cm 3 It has a compressed density of

[0022] Preferably, the present invention relates to a first median diameter D50 A is 4 to 15 μm, preferably 5 μm to 10 μm, and more preferably 5, 6, 7, 8, 9, 10 μm, or any value therebetween.

[0023] Preferably, the present invention relates to a first lithium transition metal oxide powder that is a single crystal powder and contains Li, metal M A ', and oxygen, metal M A ' is a compound represented by the general formula: Ni 1-xa-ya-za Mn xa Co ya A'za The present invention provides a cathode active material according to a first aspect of the present invention, wherein 0.00≦xa≦0.30, 0.0501≦ya≦0.20, and 0.00≦za≦0.01, and A′ includes one or more elements selected from B, Ba, Sr, Mg, Al, Nb, Ti, W, F, and Zr. More preferably, 0.05≦xa≦0.30, 0.04≦ya≦0.20, and 0.00≦za≦0.01.

[0024] The compositions, i.e., the subscripts xa, ya, and za, can be determined by known analytical methods such as inductively coupled plasma-optical emission spectrometry (ICP-OES).

[0025] Preferably, the present invention relates to a second median diameter D50 B The positive electrode active material according to the first aspect of the present invention has a particle size of 0.5 μm to 2 μm, preferably 0.5 μm to 1.5 μm.

[0026] Preferably, the present invention relates to a second lithium transition metal oxide powder comprising Li, metal M B ', and oxygen, M B ' is a compound represented by the general formula Ni 1-xb-yb-zb Mn xb Co yb A'' zb The present invention provides a cathode active material according to a first aspect of the present invention, wherein A″ comprises one or more elements selected from B, Ba, Sr, Mg, Al, Nb, Ti, W, F, and Zr, and more preferably, 0.05≦xb≦0.30, 04≦yb≦0.20, and 0.00≦zb≦0.01.

[0027] In a second aspect, the present invention provides a method for producing a cathode active material, preferably a cathode active material according to the first aspect of the present invention, comprising: AThe first lithium transition metal oxide powder having a volume-based particle size distribution of 3 μm to 15 μm is subjected to a second median diameter D50 determined by laser diffraction particle size distribution analysis. B a step of mixing the first lithium transition metal oxide powder and a second lithium transition metal oxide powder having a volume-based particle size distribution of 0.5 μm to 3 μm, wherein the first lithium transition metal oxide powder and the second lithium transition metal oxide powder are both single crystal powders, and a weight fraction φ of the second lithium transition metal oxide powder relative to the total weight of the positive electrode active material is B is 5% by weight to 40% by weight.

[0028] Preferably, the weight fraction φ of the second lithium transition metal oxide powder relative to the total weight of the positive electrode active material B is 15% by weight to 30% by weight, preferably 20% by weight to 25% by weight. A and the second median diameter D50 B Ratio to (D50 A / D50 B ) is 2 to 20, preferably 4 to 10, and more preferably 6 to 8.

[0029] In a third aspect, the present invention provides a battery cell comprising an active cathode material according to the first aspect of the present invention.

[0030] In a fourth aspect, the present invention provides the use of an active cathode material according to the first aspect of the present invention in a battery of any one of a portable computer, a tablet, a mobile phone, an electric vehicle, and an energy storage system.

[0031] The particle size distribution of a mixture can be readily calculated from the particle size distributions of the components of the mixture. Thus, the present invention can alternatively be defined by the following clauses:

[0032] Clause 1. A positive electrode active material for a lithium ion rechargeable battery, the positive electrode active material for a lithium ion rechargeable battery comprising Li, a metal M', and oxygen, the metal M' comprising Ni, Co, either Mn or Al, and optionally one or more elements selected from B, Ba, Sr, Mg, Nb, Ti, W, F, and Zr, the powder being a single crystal powder, the powder being characterized in that the overall particle size distribution by volume is a multimodal particle size distribution. a first partial particle size distribution having a first peak particle size and forming a first volume fraction of the overall particle size distribution, and a second partial particle size distribution having a second peak particle size and forming a second volume fraction of the overall particle size distribution, the first peak particle size being 4 μm to 15 μm, the second peak particle size being 0.5 μm to 2 μm, and the second fraction being 5 vol % to 40 vol % of the overall particle size distribution.

[0033] Item 2. The positive electrode active material according to item 1, wherein a ratio of the first peak particle size to the second peak particle size is 2 to 20.

[0034] Item 3. The positive electrode active material according to item 1, wherein a ratio of the first peak particle size to the second peak particle size is 4 to 10, preferably 6 to 8.

[0035] Item 4. The positive electrode active material according to any one of Items 1 to 3, wherein the first peak particle size is 5 μm to 10 μm.

[0036] Item 5. The positive electrode active material according to any one of Items 1 to 4, wherein the second peak particle size is 0.5 μm to 1.5 μm.

[0037] Clause 6. The positive electrode active material according to any one of clauses 1 to 5, wherein the second fraction is 15% by volume to 30% by volume, preferably 15% by volume to 30% by volume, of the overall particle size distribution.

[0038] Clause 7. The positive electrode active material has a density of at least 3.50 g / cm 3 7. The positive electrode active material according to any one of items 1 to 6, having a compressed density of

[0039] Clause 8. The cathode active material of any one of clauses 1 to 7, wherein particles in the first volume fraction have a different composition than a composition of particles in the second volume fraction.

[0040] Clause 9. The particles in the first volume fraction are Li, metal M A ' and oxygen, and has the general formula Ni 1-xa-ya-za Mn xa Co ya A' za M A 9. The cathode active material of any one of clauses 1 to 8, wherein A′ is 0.00≦xa≦0.30, 0.01≦ya≦0.20, and 0.00≦za≦0.01, and A′ includes one or more elements selected from Mn, B, Ba, Sr, Mg, Al, Nb, Ti, W, F, and Zr.

[0041] Clause 10. The particles in the second volume fraction are Li, metal M B ', and oxygen, M B ' is a compound represented by the general formula Ni 1-xb-yb-zb Mn xb Co yb A'' zb 10. The cathode active material of any one of clauses 1-9, wherein 0.00≦xb≦0.35, 0.01≦yb≦0.35, and 0≦zb≦0.01; and A″ includes one or more elements selected from B, Ba, Sr, Mg, Al, Nb, Ti, W, F, and Zr.

[0042] Clause 11. The powder has a median diameter D50 of 4 μm to 15 μm as determined by laser diffraction particle size distribution analysis. A The first lithium transition metal oxide powder having a particle size distribution having a median diameter D50 of 0.5 μm to 2 μm as determined by laser diffraction particle size distribution analysis. B 11. The positive electrode active material according to any one of claims 1 to 10, obtained by mixing with a second lithium transition metal oxide powder having a particle size distribution having a particle size distribution of:

[0043] Clause 12. The positive electrode active material according to any one of clauses 1 to 11, wherein the powder is obtained by mixing a first lithium transition metal oxide powder having a particle size distribution corresponding to the first partial particle size distribution with a second lithium transition metal oxide powder having a particle size distribution corresponding to the second partial particle size distribution.

[0044] Clause 13. The positive electrode active material according to any one of clauses 1 to 12, wherein the positive electrode active material comprises the first volume fraction and the second volume fraction.

[0045] Clause 14. The positive electrode active material according to any one of clauses 1 to 13, wherein the first volume fraction is 5 volume % to 40 volume % of a sum of the first volume fraction and the second volume fraction.

[0046] Clause 15. The method for producing a positive electrode active material according to any one of clauses 1 to 14, further comprising: A The first lithium transition metal oxide powder having a volume-based particle size distribution of 4 μm to 15 μm is subjected to a laser diffraction particle size distribution analysis. B a step of mixing the first lithium transition metal oxide powder and a second lithium transition metal oxide powder having a volume-based particle size distribution of 0.5 μm to 2 μm, wherein the first lithium transition metal oxide powder and the second lithium transition metal oxide powder are both single crystal powders, and a weight fraction φ of the second lithium transition metal oxide powder relative to the total weight of the positive electrode active material is B is 5% by weight to 40% by weight.

[0047] Clause 16. The weight fraction φ of the second lithium transition metal oxide powder relative to the total weight of the positive electrode active material B 16. The method according to claim 15, wherein the amount of the hydroxyl group is 15% by weight to 30% by weight, preferably 20% by weight to 25% by weight.

[0048] Clause 17. A battery cell comprising the positive electrode active material according to any one of clauses 1 to 14.

[0049] Clause 18. Use of the positive electrode active material according to any one of clauses 1 to 14 in a battery of any one of a portable computer, a tablet, a mobile phone, an electric vehicle, and an energy storage system.

[0050] In such cathode active materials according to any of the above provisions, the first and second peak particle sizes can be easily determined visually from a measured particle size distribution, typically measured by, for example, laser diffraction, and, if necessary, known peak deconvolution algorithms can be used. EXAMPLES

[0051] The following examples are intended to further clarify the invention, but are not intended to limit the scope of the invention.

[0052] 1. Description of analytical method 1.1. Inductively Coupled Plasma The composition of the positive electrode active material powder is measured by inductively coupled plasma (ICP) method using an Agilent 720 ICP-OES (Agilent Technologies, https: / / www.agilent.com / cs / library / brochures / 5990-6497EN%20720-725_ICP-OES_LR.pdf). One gram of powder sample is dissolved in 50 mL of high purity hydrochloric acid (at least 37 wt% HCl with respect to the total weight of the solution) in an Erlenmeyer flask. The flask is covered with a watch glass and heated on a hot plate at 380 °C until the powder is completely dissolved. After cooling to room temperature, the solution from the Erlenmeyer flask is poured into a first 250 mL volumetric flask. The first volumetric flask is then filled with deionized water up to the 250 mL mark, followed by a complete homogenization process (first dilution). Pipette an appropriate amount of the solution from the first volumetric flask and transfer it to a second 250 mL volumetric flask for the second dilution, fill the second volumetric flask to the 250 mL mark with the internal standard and 10% hydrochloric acid, then homogenize. Finally, use this solution for ICP measurement.

[0053] 1.2. Compressed Density The pressed density is measured as follows: 3 grams of powder are loaded into a pellet die with a diameter "d" of 1.30 cm. A uniaxial load of 207 MPa pressure is applied to the powder in the pellet die for 30 seconds. After the load is released, the thickness "t" of the pressed powder is measured. The pellet density is then measured in g / cm. 3 In (3 / (π*(d / 2) 2 *t)).

[0054] 1.3. SEM (Scanning Electron Microscope) Analysis The morphology of the positive electrode active material is analyzed by scanning electron microscopy (SEM) technique. This measurement is 9.6×10 -5 This is performed using a JEOL JSM7100F under a high vacuum environment of 100 Pa.

[0055] 1.4. Particle size distribution The particle size distribution (PSD) of the cathode active material powders is measured by laser diffraction particle size distribution analysis using a Malvern Mastersizer 3000 equipped with a Hydro MV wet dispersion accessory (https: / / www.malvernpanalytical.com / en / products / product-range / mastersizer-range / mastersizer-3000#overview) by dispersing each powder sample in an aqueous medium. Sufficient ultrasonic irradiation and stirring are applied and appropriate surfactants are introduced to improve the dispersion of the powders. D50 is defined as the particle size at 50% of the cumulative volume % distribution obtained from the Malvern Mastersizer 3000 by Hydro MV measurements. Similarly, D10 and D90 are defined as the particle size at 10% and 90% of the cumulative volume % distribution, respectively.

[0056] 2. Examples and Comparative Examples Comparative Example 1 A single crystal positive electrode active material, labeled CEX (Comparative) 1.1, is prepared according to the following steps.

[0057] Step 1) Preparation of transition metal hydroxide precursor: transition metal with the general formula Ni 0.62 Mn 0.18 Co 0.20 Nickel-based transition metal hydroxide powder (TMH1) with a median diameter (D50) of 4 μm is prepared by co-precipitation method in a large-scale continuous stirred tank reactor (CSTR) with mixed nickel manganese cobalt sulfate, sodium hydroxide, and ammonia.

[0058] Step 2) First Mixing: TMH1 prepared in step 1) is mixed with LiOH in an industrial blender to obtain a first mixture with a lithium to metal ratio (Li / Ni+Mn+Co) of 0.90.

[0059] Step 3) First calcination: The first mixture from step 2) is calcined in a furnace under an O2-containing atmosphere at 750°C for 12 hours to obtain a first calcined powder.

[0060] Step 4) Second Mixing: The first calcined powder from step 3) is blended with LiOH in an industrial blender to obtain a second mixture with a lithium to metal ratio (Li / Ni+Mn+Co) of 1.045.

[0061] Step 5) Second calcination: The second mixture from step 4) is calcined in a furnace in an O2-containing atmosphere at 840°C for 12 hours to obtain a second calcined powder.

[0062] Step 6) Post-treatment: The second calcined powder from step 5) is ground by a wet ball milling process to avoid the formation of agglomerates. The final product is a single crystal oxide powder labeled CEX1.1.

[0063] The particle size distribution of CEX1.1 was determined and had a D10 of 0.15 μm, a D50 of 1.12 μm, and a D90 of 2.01 μm.

[0064] CEX1.2 is prepared according to the same method as CEX1.1, except that the second firing condition in step 5) is 860° C. for 10 hours.

[0065] The particle size distribution of CEX1.2 was determined and had a D10 of 1.08 μm, a D50 of 1.76 μm, and a D90 of 2.82 μm.

[0066] CEX1.3 is prepared according to the same method as CEX1.1, except that the second firing condition in step 5) is 880° C. for 10 hours.

[0067] The particle size distribution of CEX1.3 was determined and had a D10 of 1.48 μm, a D50 of 2.46 μm, and a D90 of 3.90 μm.

[0068] CEX1.4 is prepared according to the same method as CEX1.1, except that the temperature of the second firing in step 5) is 920° C. for 10 hours.

[0069] The particle size distribution of CEX1.4 was determined and had a D10 of 2.48 μm, a D50 of 4.17 μm, and a D90 of 6.68 μm.

[0070] A single crystal positive electrode active material, labeled CEX1.5, is prepared according to the following steps.

[0071] Step 1) Preparation of transition metal hydroxide precursor: transition metal with the general formula Ni 0.62 Mn 0.18 Co 0.20 Nickel-based transition metal hydroxide powder (TMH2) with a median diameter (D50) of 10 μm is prepared by co-precipitation method in a large-scale continuous stirred tank reactor (CSTR) with mixed nickel manganese cobalt sulfate, sodium hydroxide, and ammonia.

[0072] Step 2) First Mixing: The TMH2 prepared in step 1) is mixed with LiOH in an industrial blender to obtain a first mixture with a lithium to metal ratio (Li / Ni+Mn+Co) of 0.85.

[0073] Step 3) First calcination: The first mixture from step 2) is calcined in a furnace under air atmosphere at 900° C. for 9 hours to obtain a first calcined powder.

[0074] Step 4) Second Mixing: The first calcined powder from step 3) is blended with LiOH in an industrial blender to obtain a second mixture with a lithium to metal ratio (Li / Ni+Mn+Co) of 1.065.

[0075] Step 5) Second calcination: The second mixture from step 4) is calcined in a furnace in air atmosphere at 960° C. for 12 hours to obtain a second calcined powder.

[0076] Step 6) Post-treatment: The second calcined powder from step 5) is ground by a wet ball milling process to avoid the formation of agglomerates. The final product is a single crystal oxide powder labeled CEX1.5.

[0077] The particle size distribution of CEX1.5 was determined and had a D10 of 4.89 μm, a D50 of 8.76 μm, and a D90 of 14.7 μm.

[0078] Example 1 EX1.1 is prepared by mixing the first transition metal oxide powder CEX1.5 with the second transition metal oxide powder CEX1.1 in an industrial blender at a fraction of the second powder of 8% by weight, the fraction of the second powder being calculated according to the following formula: (weight of second powder / (weight of second powder + weight of first powder)) * 100%.

[0079] EX1.2, EX1.3, EX1.4 and EX1.5 are prepared according to the same method as EX1.1, except that the fraction of the second powder is 12, 20, 25 and 30% by weight, respectively.

[0080] Example 2 EX2 is prepared in the same manner as EX1.4, except that CEX1.2 is used as the second transition metal oxide powder.

[0081] Example 3 EX3.1 is prepared according to the same method as EX1.1, except that CEX1.3 is used as the second transition metal oxide powder, the fraction of the second powder being 25% by weight.

[0082] EX3.2 is prepared according to the same method as EX1.1, except that CEX1.3 is used as the second transition metal oxide powder, the fraction of the second powder being 30% by weight.

[0083] Example 4 The positive electrode active material labeled EX4.1 is a mixture of EX4-A and EX4-B prepared according to the following steps.

[0084] Step 1) Prepare the single crystal positive electrode active material, EX4-A, according to the following procedure. a. Preparation of transition metal hydroxide precursor: transition metal with the general formula Ni 0.86 Mn 0.10 Co 0.04 Nickel-based transition metal hydroxide powder (TMH5) with a median diameter (D50) of 5 μm is prepared by co-precipitation method in a large-scale continuous stirred tank reactor (CSTR) with mixed nickel manganese cobalt sulfate, sodium hydroxide, and ammonia. b. First Mixing: TMH5 prepared in step 1.a) is mixed with LiOH in an industrial blender to obtain a first mixture with a lithium to metal ratio (Li / Ni+Mn+Co) of 0.90. c. First calcination: The first mixture from step 1.b) is calcined in a furnace under O2-containing atmosphere at 720°C for 10 hours to obtain the first calcined powder. d. Second Mixing: The first calcined powder from step 1.c) is blended with LiOH in an industrial blender to obtain a second mixture with a lithium to metal ratio (Li / Ni+Mn+Co) of 1.06. e. Second calcination: The second mixture from step 1.d) is calcined in a furnace in an O2-containing atmosphere at 830°C for 12 hours to obtain a second calcined powder. f. Post-treatment: The second calcined powder from step 1.e) is ground by wet ball milling process for 10 hours to avoid the formation of agglomerates. The final product is a single crystal oxide powder labeled EX4-A.

[0085] Step 2) Prepare the single crystal positive electrode active material, EX4-B, according to the following procedure. a. Preparation of transition metal hydroxide precursor: transition metal with the general formula Ni 0.86 Mn 0.10 Co 0.04 Nickel-based transition metal hydroxide powder (TMH6) with a median diameter (D50) of 5 μm is prepared by co-precipitation method in a large-scale continuous stirred tank reactor (CSTR) with mixed nickel manganese cobalt sulfate, sodium hydroxide, and ammonia. b. First Mixing: TMH6 prepared in step 2.a) is mixed with LiOH in an industrial blender to obtain a first mixture with a lithium to metal ratio (Li / Ni+Mn+Co) of 0.90. c. First calcination: The first mixture from step 2.b) is calcined in a furnace under O2-containing atmosphere at 720°C for 10 hours to obtain the first calcined powder. d. Second Mixing: The first calcined powder from step 2.c) is blended with LiOH in an industrial blender to obtain a second mixture with a lithium to metal ratio (Li / Ni+Mn+Co) of 1.01. e. Second calcination: The second mixture from step 2.d) is calcined in a furnace in an O2-containing atmosphere at 950°C for 12 hours to obtain a second calcined powder. f. Post-treatment: The second calcined powder from step 2.e) is ground by wet ball milling process for 6 hours to avoid the formation of agglomerates. The final product is a single crystal oxide powder, labeled EX4-B.

[0086] EX4-A had a D50 of 1.3 μm and EX4-B had a D50 of 7.1 μm.

[0087] Step 3) Preparation of EX4.1: EX4-A and EX4-B are mixed in a weight ratio between EX4-A and EX4-B of 25% by weight:75% by weight. The product is labeled as EX4.1.

[0088] EX4.2 is prepared according to the same method as EX4.1, except that the weight ratio of EX4-A to EX4-B is 70 wt%:30 wt%.

[0089] EX5.1 is prepared according to the same method as EX1.4, except that CEX1.4 is used as the first transition metal oxide powder.

[0090] EX5.2 is prepared according to the same method as EX1.5, except that CEX1.4 is used as the first transition metal oxide powder.

[0091] In all examples, the composition of the components in the final product is the same, and therefore the densities of those components are the same, so that a particular weight ratio of components in the final product corresponds to a numerically identical volume ratio of those components in the final product.

[0092] It is not necessary to measure the particle size distribution of the final product, but it can be readily calculated from the particle size distributions of the constituent components and their relative proportions.

[0093] FIG. 1 shows an SEM image of EX1.4, which contains a first single crystal powder and a second single crystal powder having different median diameters.

[0094] Table 1 summarizes the compositions of the examples and comparative examples and their corresponding pressed densities.

[0095] [Table 1]

[0096] CEX1.1 to CEX1.5 are single crystal lithium transition metal oxide powders having a D50 in the range of 1.1 μm to 8.7 μm. The single crystal lithium transition metal oxide powders used alone have a compressed density of 3.40 g / cm 3 Since the above-mentioned method does not exceed the above range, it is believed that the present invention cannot meet the object of the present invention.

[0097] EX1.1, EX1.2, EX1.3, EX1.4, and EX1.5 are different fractions of φ from CEX1.5. B The mixtures of CEX1.1 with CEX1.1 (fraction of second powder). They all have higher pressed density than CEX1.5. As can be clearly seen from Figure 2, the pressed density is further optimized when the fraction of second powder is 20%-25% by weight.

[0098] EX1.4, EX2, and EX1.3 are mixtures of CEX1.5 (as the first powder) with CEX1.1, CEX1.2, and CEX1.3 (as the second powder), respectively, with the fraction of the second powder φ B The pressed density of all the examples is higher than that of CEX1.5. As can be clearly seen from FIG. 3, the pressed density is proportional to the median diameter (D50) of the first powder. A ) and second powder median diameter (D50 B ) or D50 A / D50 B When it is 4.0 or more, more preferably 6 to 8, it is further optimized.

[0099] EX4.1 and EX4.2 have a higher molar content of Ni relative to the total molar content of transition metals than the other above mentioned examples. EX4.1 and EX4.2 meet the objectives of the present invention.

[0100] EX5.1 and EX5.2 are mixtures of CEX1.4 (as the first powder) and CEX1.1 (as the second powder), both of which show higher pressed density compared to the comparative examples, thus exceeding the objectives of the present invention.

Claims

1. A positive electrode active material for a lithium ion rechargeable battery, comprising: the positive electrode active material includes Li, a metal M', and oxygen, the metal M' includes Ni, Co, either Mn or Al, and optionally one or more elements selected from B, Ba, Sr, Mg, Nb, Ti, W, F, and Zr; the positive electrode active material is a mixture of lithium transition metal oxide powders, the mixture comprises a first lithium transition metal oxide powder and a second lithium transition metal oxide powder, both of which are single crystal powders; The first lithium transition metal oxide powder has a first weight fraction φ of the positive electrode active material. A and a first median diameter D50 of 3 μm to 15 μm as determined by laser diffraction particle size distribution analysis. A having The second lithium transition metal oxide powder has a second weight fraction φ of the positive electrode active material. B and a second median diameter D50 of 0.5 μm to 1.7 μm as determined by laser diffraction particle size distribution analysis. B having Said second weight fraction φ B is 5% by weight to 40% by weight.

2. The first median diameter D50 A The positive electrode active material according to claim 1, wherein the average particle diameter is 4 μm to 15 μm.

3. The first median diameter D50 A and the second median diameter D50 B The positive electrode active material according to claim 1 or 2, wherein the ratio of

4. The first median diameter D50 A and the second median diameter D50 B The positive electrode active material according to any one of claims 1 to 3, wherein the ratio of

5. The first median diameter D50 A The positive electrode active material according to any one of claims 1 to 4, wherein the thickness is 5 µm to 10 µm.

6. The second median diameter D50 B The positive electrode active material according to any one of claims 1 to 5, wherein the average particle size is 0.5 µm to 1.5 µm.

7. Said second weight fraction φ B The positive electrode active material according to any one of claims 1 to 6, wherein the content of the cation is 15% by weight to 30% by weight.

8. The positive electrode active material has a compressibility of at least 3.50 g / cm after applying a uniaxial pressure of 207 MPa for 30 seconds. 3 The positive electrode active material according to any one of claims 1 to 7, having a compressed density of

9. The first lithium transition metal oxide powder is A ', and oxygen, M A ' is a compound represented by the general formula Ni 1-xa-ya-za Mn xa Co ya A' za 9. The positive electrode active material according to claim 1, wherein 0.00≦xa≦0.30, 0.01≦ya≦0.20, and 0.00≦za≦0.01, and A′ includes one or more elements selected from Mn, B, Ba, Sr, Mg, Al, Nb, Ti, W, F, and Zr.

10. The second lithium transition metal oxide powder is B ' and oxygen, B ' is a compound represented by the general formula Ni 1-xb-yb-zb Mn xb Co yb A'' zb wherein 0.00≦xb≦0.35, 0.01≦yb≦0.35, and 0≦zb≦0.01; and A″ comprises one or more elements selected from B, Ba, Sr, Mg, Al, Nb, Ti, W, F, and Zr. The positive electrode active material according to any one of claims 1 to 9.

11. The first weight fraction φ A and the second weight fraction φ B The positive electrode active material according to any one of claims 1 to 10, wherein the sum of is at least 95%.

12. A method for producing a positive electrode active material, comprising: A The first lithium transition metal oxide powder having a volume-based particle size distribution of 3 μm to 15 μm is subjected to a second median diameter D50 B a weight fraction φ of the second lithium transition metal oxide powder relative to the total weight of the positive electrode active material, the weight fraction φ of the second lithium transition metal oxide powder being 0.5 μm to 1.7 μm; B is 5% to 40% by weight.

13. The weight fraction φ B The method of claim 12, wherein the amount of the hydroxyl group is 15% to 30% by weight.

14. The method according to claim 12 or 13, wherein the positive electrode active material is the positive electrode active material according to any one of claims 1 to 11.

15. A battery cell comprising the positive electrode active material according to any one of claims 1 to 11.

16. Use of the positive electrode active material according to any one of claims 1 to 11 in a battery of any one of a portable computer, a tablet, a mobile phone, an electric vehicle, and an energy storage system.

Citation Information

Patent Citations

  • Positive active material, and positive electrode and lithium battery including the positive active material

    JP2011216485A

  • Electrochemical element electrode and lithium ion secondary battery

    JP2012054135A

  • Positive electrode active material for lithium ion battery, positive electrode for lithium ion battery, and lithium ion battery

    JP2016122626A

  • Lithium secondary battery

    US20190221830A1

  • Positive electrode active material for nonaqueous electrolyte secondary battery, positive electrode and secondary battery

    WO2008078784A1